Proposal of the evaluation system of preparedness of businesses for implementation of an innovation strategy - Lendel, Viliam; Varmus, Michal (Business: Theory and Practice, 2012)
Development and implementation of innovation strategy requires increased attention of the businesses. Rather than the business acceding to its implementation needs to know the current status of work in innovation and the key elements that will be crucial in this process. The aim of this paper is based on the analysis of literary sources and carried out research on the proposal of the evaluation system of preparedness of businesses for implementation of an innovation strategy. The proposal describes different levels of preparedness, the basic evaluation methodology and evaluation procedure. The paper brings the main results of the authors who conducted research on a sample of 462 respondents to show the current situation in the Slovak businesses in the use of innovation strategy. A survey used the following methods: comparative method, qualitative evaluation, and method of structured and semi-structured interviews, observation methods, method of document analysis (a method of content analysis) and the questionnaire method.